Children's and young adult literature by Latino writers : a guide for librarians, teachers, parents, and students - York, Sherry, 1947- (Worthington, Ohio : Linworth Pub., 2002)
Provides publication and review information on children's and young adult novels, short stories, folklore, drama, poetry, anthologies, and nonfiction written by Latinos.
Includes bibliographical references and index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
Professional
Keywords: American literature -- Hispanic American authors -- Bibliography; Children's literature, American -- Bibliography; Hispanic Americans in literature -- Bibliography; Hispanic Americans -- Bibliography; Hispanic Americans -- Juvenile literature -- Bibliography; Young adult literature, American -- Bibliography; American literature -- Hispanic American authors -- Bibliography; Children's literature -- Bibliography; Hispanic Americans in literature -- Bibliography; Hispanic Americans -- Bibliography; Hispanic Americans -- Juvenile literature -- Bibliography; Young adult literature -- Bibliography